An evaluation of the relationships between fecal nitrogen and digestibility, crude protein and dry matter intake of forage. - Ngugi, K.R. (Texas A&M University, 1982)
Fresh live oak leaves (Quercus spp) were mixed with fair quality alfalfa hay to Form Four rations containing 0, 25, 50 and 75 liveoak leaves on as fed weight basis. Their rations were fed to four Spanish goats in a 4x4 Latin square sequence. Relationships between fecal nitrogen and the dry matter intake, total nitrogen intake, and dry matter digestibility were evaluated. Daily feed intake, fecal output, and nitrogen balance were determined for each ration. In vivo percentage digestibilities of dry matter, organic matter and nitrogen were calculated. In vitro digestibility coefficients for ration organic matter were also determined. Feed and detergent fiber NDF, acid detergent fiber ADF, and acid detergent fiber nitrogen ADFN. Fecal nitrogen output expressed as either grams per day or percentage nitrogen, exhibited no significant (p< .05) relationship to either percentage digestibility, dietary nitrogen, total nitrogen intake or organic matter intake. However, percentage dietary nitrogen PDN, total nitrogen intake (TNI), and percentage nitrogen digested (PND) decreased significantly (P< .05) as the level of liveoak leaves in the diets increased. Urinary nitrogen (UN) in g/d varied among treatments and decreased with increase in the level of liveoak leaves (P< .05). Digestibility values differed among treatments; in vitro methods gave higher digestibility values for rations on (0% liveoak) and two (25% Liveoak) and significantly (P<. 05) lower value for ration four (75% liveoak). Treatment effects for in vivo organic matter digestibility were only significant at P= .3 level. OMI was similar for rations one, two and three; however, addition of more than 50% liveoak leaves to the diets resulted in a significant (P< 0.05) decrease in OMI. NDF and ADF of feed and feces were positively related to the level of liveoak leaves. However, ADEN showed a positive relationship to OMD. This relationship suggested that by correcting total FN for bound N, then FNI technique may be used to predict digestibilities of browse-containing rations. This approach requires more data for validation.